Numerical and experimental investigation of acoustic agglomeration - Low, Aik How (2019)
Acoustic Agglomeration is a pre-treatment method use for coagulating dust particles for effective air filtration. It uses acoustic waves to collide dust particles, forming larger dust particles size and the agglomerated dust particles are filtered using air filters, wet precipitator or other conventional filtration methods. The study examines the parametric values required to achieve high aerosol agglomeration using acoustic waves. This study describes the agglomeration efficiency in aerosol at sound frequency 4 kHz to 10 kHz, ambient pressure between 500 kPa to 1,100 kPa, ambient temperature from 400 K to 1,000 K, Sound Pressure Level (SPL) from 100 dB to 155 dB and mass loading in 8.46 g/m3 to 20.46 g/m3. The investigation was conducted through numerical simulations using sectional methods to determine the optimal values of the operating parameters. Demonstration and experiment were conducted in this study to examine the flow pattern of the aerosol during acoustic agglomeration process. The study found that the maximum agglomeration efficiency through adjustment of the operating parameters. The numerical simulation shows that attaining the highest possible value for ambient temperature, SPL and mass loading could increase the agglomeration efficiency in particles, while keeping ambient pressure at its minimum value shows better agglomeration efficiency. The results show indication that the optimal value for sound frequency is greatly dependent other operating parameters. The demonstration exhibits turbulence flow motion in aerosol during agglomeration process. This study concludes effect of the operating parameters on acoustic agglomeration and the parametric values in achieving the maximum agglomeration efficiency in aerosol.